Respuesta :
Answer:
[tex]-26x^2+56x-15[/tex]
Step-by-step explanation:
[tex]3x(-2x + 7) - 5(x - 1)(4x - 3)[/tex]
Expand the brackets:
[tex]\implies -6x^2+21x-5(4x^2-7x+3)[/tex]
[tex]\implies -6x^2+21x-20x^2 +35x-15[/tex]
Collect like terms:
[tex]\implies -6x^2-20x^2+21x +35x-15[/tex]
Combine like terms:
[tex]\implies -26x^2+56x-15[/tex]
Answer:
Step-by-step explanation:
This is late reply. You can try searching online next time you need an answer in a hurry - most questions have been asked before: like here https://brainly.com/question/11412899
3x(-2x + 7) - 5(x - 1)(4x - 3)
= (-6x^2 + 21x) - 5(4x^2- 7x +3)
= -6x^2 + 21x - 20x^2 + 35x - 15
= -26x^2 + 56x -15